Determinants of Investment Decisions in the Capital Market: A Case Study in Public Education Participants - Luthviana, Dewi Nurika Sari; Murdiyanto, Edi; Akbar, Taufik (Universitas Islam Kadiri, 2024)
The purpose of this study is to determine the factors that influence investment decisions in the capital market. Data was obtained directly from the distribution of questionnaires to public education participants. The population in this study is all participants of Capital Market-Public Education. The sample used in this study is by using probability sampling with a simple random sampling method or simple random sample. This type of research is quantitative research using Partial Least Square (PLS) analysis techniques. The inner model and outer model were used in this study, with the inner model useful for testing the quality of hypotheses, while the outer model for testing validity and reliability. Based on data processing from data that has been collected through questionnaires, and has passed the process of analysis and discussion, it can be concluded that all variables have a significant direct influence except for the Financial Literacy variable. While indirect influence shows that Lifestyle variables are able to mediate all variables used in this study.